Dual-Channel Green Supply Chain Decision-Making and Coordination considering CSR and Consumer Green Preferences - Xiaochun Chen; Rui Zhang; Bo Lv (Discrete Dynamics in Nature and Society)
With the rapid development of the Internet and changes in consumer buying habits, many manufacturers are increasingly relying on online channels to sell their products as opposed to traditional retail channels. In this study, we innovatively investigate the impact of corporate social responsibility (CSR) and consumer green preferences (CGP) on supply chain performance and product green level in the dual-channel green supply chain (DCGSC). Specifically, four models of DCGSC (centralized, independent CSR, cooperative CSR, and collaboration contract) are investigated. Next, we use game theory to investigate the optimal product green level, online and offline selling prices, social welfare, profits of supply chain enterprises, and the whole supply chain under the four models. We give numerical examples to demonstrate the effectiveness and viability of the four models. We find several interesting conclusions. First, increasing the attention to both CSR and CGP by supply chain enterprises is conducive to stimulating innovation and improving product green level. Second, when supply chain enterprises actively execute their CSR, they can reasonably control online and offline selling prices and increase consumer surplus and the profits of whole supply chain and social welfare are increased. Third, it is beneficial to increase the value of supply chain enterprises to enhance CSR within a certain threshold, but when CSR is higher than the threshold, the profitability of supply chain enterprises is weakened. Finally, collaboration contracts are capable of coordinating DCGSC and guaranteeing the profitability of supply chain enterprises.